2004
DOI: 10.1002/mus.20140
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory demyelinating polyradiculoneuropathy with autonomic involvement

Abstract: We report a case of chronic acquired neuropathy predominantly affecting sensory and autonomic nerves. Investigations showed a demyelinating polyradiculoneuropathy with axonal degeneration and depletion of postganglionic noradrenergic fibers in the rectal mucosa. Intravenous immunoglobulin and corticosteroid administration were effective in alleviating symptoms and improving electrophysiological abnormalities. This neuropathy may be a novel variant of chronic inflammatory demyelinating polyradiculoneuropathy (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Dysautonomia in CIDP has been attributed to the involvement of postganglionic unmyelinated autonomic fibers. Autoimmunity in CIDP is not only directed against myelin but also against axon and autonomic ganglia [7]. In our study, 2 of the 3 patients with dysautonomia had diabetes mellitus suggesting the role of diabetes in producing dysautonomia in CIDP.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Dysautonomia in CIDP has been attributed to the involvement of postganglionic unmyelinated autonomic fibers. Autoimmunity in CIDP is not only directed against myelin but also against axon and autonomic ganglia [7]. In our study, 2 of the 3 patients with dysautonomia had diabetes mellitus suggesting the role of diabetes in producing dysautonomia in CIDP.…”
Section: Discussionmentioning
confidence: 87%
“…In the literature some studies have demonstrated minimal subclinical autonomic dysfunction [20, 21]. In the European Federation of Neurological Societies/Peripheral Nerve Society CIDP Guideline dysautonomia was not mentioned in atypical CIDP but we considered it atypical in the light of another report [7]. Dysautonomia in CIDP has been attributed to the involvement of postganglionic unmyelinated autonomic fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto and colleagues reported a case of chronic acquired neuropathy predominantly affecting sensory and autonomic nerves suggesting that autonomic nerve involvement does not exclude a diagnosis of CIDP [61]. Severe autonomic dysfunction with abnormal autonomic tests function has been reported in a chronic axonal subtype of CIDP [62].…”
Section: Subacute and Chronic Neuropathies With Immune-mediated Mementioning
confidence: 99%
“…In cases with inflammation mainly affecting the dorsal roots sensory nerve-conduction studies may be normal while somatosensory-evoked potentials, elevated cerebrospinal fluid protein content and enlargement of lumbar nerve roots on MRI were the characteristic features of the syndrome termed chronic immune sensory polyradiculopathy [31 ]. Mild autonomic dysfunction is not uncommon in CIDP [33] and, in rare cases, severe autonomic disturbance may even be the presenting feature [34]. A comprehensive comparison of the different forms of sensory neuropathy including paraneoplastic, dysimmune, autoimmune, toxic and hereditary sensory neuropathy (=Friedreich's ataxia) has been provided by Kuntzer and coworkers [32].…”
Section: Pathogenesis and Histopathological Findingsmentioning
confidence: 99%